KAJIAN PUSTAKA PEMBERIAN SPORT MASSAGE DAN STRETCHING TERHADAP PEMULIHAN KELELAHAN OTOT DAN KADAR ASAM LAKTAT PADA ATLET - Mulya, Dimas Yuzril; Suwondo, Ari; Setyaningsih, Yuliani (Jurnal Kesehatan Masyarakat (Undip), 2021)
Physical fatigue in sports activities, caused by several factors including intensity, frequency, and duration of training that causes a lack of energy and the accumulation of lactic acid from metabolic waste resulting in muscle fatigue. This study aimed is to analyze sports massage and stretching on the recovery of muscle fatigue and lactic acid levels in athletes. This type of research is a quantitative descriptive study using the Literature Review Comparative Study method. This research was sourced from 13 articles related to the analysis of sports massage and stretching on muscle fatigue and lactic acid levels in athletes obtained in the journal portal namely Garuda (Garba Rujukan Digital), Science Direct, Scopus, ClinicalKey, SpringerLink, and Google Scholar. The results of this study indicate that sports massage provides the effect of recovering muscle fatigue (after intervention for up to 7 days thereafter) and lactic acid levels (effective in men) while stretching has no significant effect. The difference between the two recovery methods lies in its function: sports massage helps to improve blood circulation while stretching focuses on increasing muscle elasticity and range of motion. Researchers suggest athletes apply sports massage regularly to reduce the risk of muscle fatigue and even muscle injury.